(untitled) (Research, Society and Development, 2022)
Disorders caused by Diabetes Mellitus (DM) manifest in the oral cavity, alter healing and immunological processes, increase susceptibility to infections and, consequently, It can affect the quality of life of these individuals. The present research aimed to evaluate the prevalence and impact of oral manifestations on the quality of life of individuals with Type 2 Diabetes Mellitus and individuals without DM. Its design was characterized as an observational and cross-sectional clinical research, which included 249 individuals with DM, of both sexes and aged from 18 years and 194 individuals without DM, of both sexes, aged between 41 and 70 years. All participants were asked the sociodemographic and behavioral questionnaires and OHIP-14, as well as the assessment of the oral clinical condition. The results of this investigation revealed a difference (p<0.05) between the groups for the variables oral manifestations and reason for the last visit to the dentist. Regarding the impact on quality of life related to oral health, there was a difference between the groups (p<0.0001) for all dimensions of the OHIP. These findings suggest that in individuals with DM there is a greater risk of developing gingival inflammation, gingival recession, early tooth loss, xerostomia, pain or burning mouth, dental caries, oral candidiasis, inflammatory papillary hyperplasia and angular cheilitis, with a greater tendency to negative impact on their Quality of Life.